2015
DOI: 10.1016/j.anucene.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

New reactor cavity cooling system having passive safety features using novel shape for HTGRs and VHTRs

Abstract: A new, highly efficient reactor cavity cooling system (RCCS) with passive safety features without a requirement for electricity and mechanical drive is proposed for high temperature gas cooled reactors (HTGRs) and very high temperature reactors (VHTRs). The RCCS design consists of continuous closed regions; one is an ex-reactor pressure vessel (RPV) region and another is a cooling region having heat transfer area to ambient air assumed at 40 ( o C). The RCCS uses a novel shape to efficiently remove the heat re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…With the same novel RCCS design, Takamatsu et al, 2018 [18] continued to investigate the heat leakage due to the heat conduction through the RCCS wall. In the previous study [16], [17], the reported heat-removal rate was approximately 3 kW/m 2 . Under the assumption that the RCCS wall heat-transfer area can be doubled, a heat flux removed by the RCCS could also be doubled at an increased thermal reactor power level.…”
Section: Air-cooled Rccsmentioning
confidence: 91%
See 2 more Smart Citations
“…With the same novel RCCS design, Takamatsu et al, 2018 [18] continued to investigate the heat leakage due to the heat conduction through the RCCS wall. In the previous study [16], [17], the reported heat-removal rate was approximately 3 kW/m 2 . Under the assumption that the RCCS wall heat-transfer area can be doubled, a heat flux removed by the RCCS could also be doubled at an increased thermal reactor power level.…”
Section: Air-cooled Rccsmentioning
confidence: 91%
“…A typical RCCS includes forced water cooling which may become unavailable during accidents. Using the HTTR in Japan as an example, Takamatsu and Hu [16], [17] proposed a new highly efficient reactor cavity cooling system (RCCS) having passive safety features without any requirement of electricity and mechanical drive, Figure 76. The RCCS design consists of two continuous closed regions: one ex-reactor RPV region and another ambient air cooling region.…”
Section: Air-cooled Rccsmentioning
confidence: 99%
See 1 more Smart Citation
“…A new RCCS with a novel shape has been proposed for implementation in the HTTR (Takamatsu and Hu, 2015). The RCCS has air as its heat transport medium.…”
Section: Proposed New Rccs With a Novel Shapementioning
confidence: 99%
“…Thus, this work proposes a new air-cooled RCCS design that does not use the chimney (stack) effect and rely on emergency power generators (Takamatsu and Hu, 2015). The design concept and analysis results are presented in the following sections.…”
Section: Introductionmentioning
confidence: 99%